PERAN DOSEN MUDA DALAM MEMBENTUK KARAKTER SOSIAL MAHASISWA DI UIN DATOKARAMA PALU - Erni Irmayanti Hamzah (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2023)
This article discusses the character of young lecturers at UIN Datokarama Palu, a description of the social character of students at UIN Datokarama Palu and the role of young lecturers in shaping the social character of students at UIN Datokarama Palu. The aim of the research is to find out the character of young lecturers at UIN Datokarama Palu, a description of the social character of students at UIN Datokarama Palu and the role of young lecturers in shaping the social character of students at UIN Datokarama Palu. The research method used is qualitative research as a research procedure that produces descriptive data in the form of written or spoken words from people whose behavior can be observed with the data collection techniques of observation, interviews and documentation. The results of the study show that the characteristics of young lecturers are commitment, competence, hard work spirit, consistency, simple spirit, ability to interact, take care of themselves and respect, and become role models for students. A description of the social character of UIN Datokarama Palu students, namely honest, sportsmanship, tolerance, discipline, independence, responsibility, respect for achievement, care about cleanliness, care for health, and friendly/communicative. The role of Young Lecturers in Forming the Social Character of UIN Datokarama Palu Students is to encourage students to respect each other, cooperate between students, and instill mutual reminders and responsibility in students, exemplary, discipline, habituation, create a conducive atmosphere, so that social character is formed in students .